RI 3212 A Study Of ?Bottom-Hole? Samples Of East Texas Crude Oil - Ben E. Lindsly (The National Institute for Occupational Safety and Health (NIOSH), 1933)
The study of "bottom-hole' samples follow,-is in natural sequence the study of samples3 obtained under high pressures at the well heads of flowing wells. The principal object of this phase of gas-solubility research, started actively in January, 1530, was to gain a more accurate knowledge of the physical and chemical characteristics of the oil-gas mixtures that exist in natural reservoirs. In possession of actual data regarding the condition of the oil; the quantity of gas liberated from solution upon dimunition of pressure; and the relative volumetric proportions of gas to oil at various pressures throughout the flow string in a well, it should be possible to predict, with a fair degree of accuracy, what physical changes these mixtures would undergo throughout the life of a pool. Such information not only is important in designing flow strings in flowing wells but is important also in solving problems relating to pumping efficiency and the power required for pumping. Although certain fundamental rata Mere obtained in the stud of samples taken at the well head, "bottom-hole" samples are more representative of subsurface mixtures of oil and gas because they are obtained at reservoir temperatures, and before the oil has had the opportunity of intermingling with extraneous gas; that is, gas which either was not in solution originally, or which was liberated from solution at some higher pressure, and later became mired with the original undissolved gas.